Utilization and value enhancement in palmyra palm (Borassus flabellifer) - A critical review - Sibi, A S; Joshi, J L; Dhanalakshmi, K; Kumar, S; Ajis , M; Yasodha, P; Sheeba , J R S; Sudagar, I P; Meenakshi, P; Jayavalli , R; Swarnakumari, N; Aruna, P (Plant Science Today, 2025)
Borassus flabellifer, commonly known as the palmyra or “Miracle Tree,” is a traditional plant with immense nutritional and economic value. With nearly 122 million palms spread across India, it holds great economic potential, as every part of the tree is useful. A wide range of value-added products-such as Neera, Nungu, Palm Jaggery, Palm Sugar, Palm Candy, Palm Fibre Composite, Palm Cola, Honey, Thavun, Muffins, Cookies, Gummy Jelly, Palm Wine, Toffee, Tuber and Palm paper can be derived from the palm. These products are not only nutritious but also support processed food industries and eco-friendly innovations. Palmyrah is a versatile plant with deep cultural and economic significance, offering considerable scope for rural development, employment generation and sustainable livelihoods. Value addition through the transformation of raw materials into high-value goods allows communities to reduce post-harvest waste, enhance income and tap into new markets. The sector’s growth can be accelerated through quality improvement, innovative packaging, branding, training, infrastructure development and supportive policies. With proper intervention, the palmyra industry can become a vital driver of inclusive and resilient economic growth in palm-abundant regions. This study aims to evaluate the sector’s potential to enhance sustainable livelihoods and regional development, focusing on the role of strategic enhancements in packaging, branding, training, infrastructure and regulation in unlocking its broader economic contributions of palmyra.